Hybrid Approach to WebRTC Videoconferencing on Mobile Devices - Bakary, Diallo; Ouamri, Abdelaziz; Keche, Mokhtar (University of Eloued جامعة الوادي, 2022)
This paper provides an in-depth comparative study and an interoperability study between a WebRTC browser-based P2P videoconferencing solution and a hybrid mobile app based one, built with the React Native framework. The comparison is in terms of CPU load, RAM occupancy and network data usage. To carry out our experiments, we designed and implemented a WebRTC P2P videoconferencing prototype, including a signaling server and two separate client applications based on the same algorithm written in JavaScript. The first application is a WebRTC web client (compatible desktop and mobile) and the second is a WebRTC React Native hybrid mobile application. According to the results obtained after several video calls performed over WLAN and LTE networks, our WebRTC hybrid app consume less CPU (~-10%) compared to the web browser-based one. The two types of applications show comparable RAM occupancies. In short, our results showed that implementing WebRTC real-time video streaming in a hybrid mobile app can be a better alternative in the WebRTC videoconferencing on mobile devices, while most of the scientific researches carried out around WebRTC still focus on the web browser.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: WebRTC · Videoconferencing · Hybrid App · Web App · CPU consumption · RAM occupancy · Bandwidth occupancy · Quality of Experience (QoE).